JSON Dataset of Simulated Building Heat Control for System of Systems Interoperability - Nilsson, Jacob (Luleå University of Technology, 2025)
Interoperability in systems-of-systems is a difficult problem due to the abundance of data standards and formats.
Current approaches to interoperability rely on hand-made adapters or methods using ontological metadata.
This dataset was created to facilitate research on data-driven interoperability solutions. The data comes from a simulation of a building heating system, and the messages sent within control systems-of-systems. For more information see attached data documentation.

The data comes in two semicolon-separated (;) csv files, training.csv and test.csv. The train/test split is not random; training data comes from the first 80% of simulated timesteps, and the test data is the last 20%. There is no specific validation dataset, the validation data should instead be randomly selected from the training data. The simulation runs for as many time steps as there are outside temperature values available. The original SMHI data only samples once every hour, which we linearly interpolate to get one temperature sample every ten seconds. The data saved at each time step consists of 34 JSON messages (four per room and two temperature readings from the outside), 9 temperature values (one per room and outside), 8 setpoint values, and 8 actuator outputs. The data associated with each of those 34 JSON-messages is stored as a single row in the tables. This means that much data is duplicated, a choice made to make it easier to use the data.

The simulation data is not meant to be opened and analyzed in spreadsheet software, it is meant for training machine learning models. It is recommended to open the data with the pandas library for Python, available at https://pypi.org/project/pandas/.

The data file with temperatures (smhi-july-23-29-2018.csv) acts as input for the thermodynamic building simulation found on Github, where it is used to get the outside temperature and corresponding timestamps. Temperature data for Luleå Summer 2018 were downloaded from SMHI.

Datasetet innehåller simulerad servicedata för system-av-system interoperabilitetsforskning. För mer information se bifogad dokumentation och den engelska katalogsidan.

Data kommer i två semikolonseparerade (;) csv-filer, training.csv och test.csv. Träning/testfördelningen är inte slumpmässig; träningsdata kommer från de första 80 % av de simulerade tidsstegen och testdata är de sista 20 %. Det finns ingen specifik valideringsdatauppsättning, valideringsdatan bör istället väljas slumpmässigt från träningsdatan. Simuleringen körs i lika många tidssteg som det finns tillgängliga utetemperaturvärden. De ursprungliga SMHI-data samplar bara en gång i timmen, som linjärt interpolerar för att få ett temperaturprov var tionde sekund. Data som sparas vid varje tidssteg består av 34 JSON-meddelanden (fyra per rum och två temperaturavläsningar utifrån), 9 temperaturvärden (ett per rum och utanför), 8 börvärden och 8 ställdonutgångar. Data som är associerade med vart och ett av dessa 34 JSON-meddelanden lagras som en enda rad i tabellerna. Detta innebär att mycket data dupliceras, ett val som görs för att göra det lättare att använda datan.

Simuleringsdata är inte avsedd att öppnas och analyseras i kalkylprogram, det är avsett att träna maskininlärningsmodeller. Det rekommenderas att öppna data med pandas-biblioteket för Python, tillgängligt på https://pypi.org/project/pandas/.

Datafil med temperaturer (smhi-july-23-29-2018.csv) för termodynamisk simulering avsedd som input vid simulering gällande utomhustemperatur och tidsmarkör. Temperaturdata från Luleå sommaren 2018 var nedladdade från SMHI.
JSON dataset för simulerad byggnadsvärmekontroll för system-av-system interoperabilitet
Keywords: interoperability; interoperabilitet; atmospheric conditions; environmental temperature; System of Systems; System av System; Cyber-physical systems; cyberfysiska system; Information Systems; Systemvetenskap, informationssystem och informatik; Building Technologies; Husbyggnad; Control Engineering; Reglerteknik; Communication Systems; Kommunikationssystem; Other Electrical Engineering, Electronic Engineering, Information Engineering; Annan elektroteknik och elektronik